University education in the 'global South': issues, challenges, opportunities and musings on the future - Rhonda Breit (University of Johannesburg, 2019)
In this editorial, issue editor Rhonda Breit introduces the five peer-reviewed articles and three thoughtful and engaging reflections in the sixth issue of the SOTL in the South journal. These papers provide insights into how universities in the 'global South' are claiming a unique space in tertiary education: a space that responds to context, a space that is responsive to dynamic change and a space that values diversity and tradition. In addition, the editorial asks what sort of university leadership is needed in order to bring the global South in from the margins. Breit includes three reflections on leadership from academic leaders working in the global South that discuss how its universities are responding to disturbances and adapting to changing ecologies. How to cite this editorial: BREIT, Rhonda Alain. University education in the 'global South': issues, challenges, opportunities and musings on the future. Scholarship of Teaching and Learning in the South. v. 3, n. 2, p. 1-9, Sept. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=118&path%5B%5D=43 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/